High micromechanical interlocking graphene oxide/carboxymethyl cellulose composite architectures for enhancing the interface adhesion between carbon fiber and epoxy. (December 2020) - Qiu, Baowei; Sun, Tong; Li, Muxuan; Chen, Yang; Zhou, Shengtai; Liang, Mei; Zou, Huawei
Graphical abstract: Highlights: Multi-scale reinforced structural design of polymer/graphene oxide/carbon fiber. Increased mechanical interlocking and chemical bonding between the fibers and the matrix. The interfacial shear strength (IFSS) and the interlaminar shear strength (ILSS) of the composite increased significantly. The bonding mechanism of multi-scale reinforced materials was analyzed. Abstract: The interface performance of carbon fiber (CF) reinforced polymer composites (CFRPs) is one of the key factors that affect their properties. In order to improve the interface adhesion between CF and epoxy (EP), a green method is proposed. Carboxymethyl cellulose (CMC) and graphene oxide (GO) are introduced to the CF surface through the hydrogen bonds, and they can form high micromechanical interlocking composite architectures, which can enhance the micromechanical interaction in the interface of CF and EP. It is found that CMC and GO can significantly improve the interfacial shear strength (IFSS) and interlaminar shear strength (ILSS) of EP/CF composite. This means that it has great potential to improve the interface of CFRPs and strengthen their performance by natural cellulose fibers. This modification method does no harm to CF and is environmental friendliness, which lays a research foundation for using natural cellulose to enhance the interface performance of CFRPs.